Pemanfaatan Alat Permainan Edukatif untuk Mengembangkan Kecerdasan Visual Spasial Anak Usia Dini - Kharida Shaleha; Khairatun Nisa (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2026)
Educational play Materials (APE) are learning aids designed to support child development through play-based activities. Early childhood is a crucial period of growth and development, requiring appropriate stimulation to optimize various aspects of a child's abilities including visual-spatial intelligence. This article aims to examine the use of educational play tools in fostering early childhood intelligence. A literature review method was employed, analyzing various books, journals, and scholarly articles related to educational play tools and early childhood education. The findings indicate that educational play tools offer significant benefits for developing visual-spatial intelligence. Through the use of these tools, children can engage in active learning, explore their environment, solve problems, and within a fun learning atmosphere understand, recognize, process, and interpret visual information and spatial relationships between objects (such as shape, size, direction, distance, and position). However, the utilization of educational play tools still faces challenges, including limited facilities, a lack of teacher competence in using the tools, and minimal parental involvement in supporting educational play activities. Therefore, collaboration among teachers, parents, and educational institutions is essential to optimize the use of these tools. Effective use of educational play tools can support holistic and balanced child development, thereby enabling early childhood education goals to be achieved optimally.